2008
DOI: 10.1007/s11682-008-9025-4
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Visuospatial Working Memory in Healthy Young Adults at Risk for Hypertension

Abstract: Family history of hypertension (FH+) has been associated with subtle deficits in cognitive function. In search of an early marker that may identify individuals predisposed to developing cognitive difficulties, we employed fMRI to test for FH+ related differences in hemodynamic response to a working memory challenge in healthy young adults with intact working memory. Fourteen healthy adults (ages 18 to 40 years) participated in an fMRI study of working memory. Seven of the participants were FH+. Groups were mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 61 publications
(83 reference statements)
1
30
1
Order By: Relevance
“…In the past, a higher task-related BOLD response at comparable levels of performance in patients with MS, HIV, and genetic risk for AD relative to healthy controls has been observed and interpreted as compensatory overactivation 25,46,47 ; however, the opposite trend (ie, lower task-related activation at similar levels of performance) has been noted in patients at high risk for cardiovascular and cerebrovascular disease. 42,[48][49][50] On the basis these observations, it may be that early in the vascular disease process, subclinical reductions in vascular responsivity and endothelial function result in lower, yet sufficient, amounts of oxygen being delivered to activated neurons, thus producing a lower BOLD response to a cognitive challenge despite intact behavioral performance. 48,49 As vascular problems worsen, further declines in cerebrovascular reactivity and microvascular damage likely lead to vascular cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, a higher task-related BOLD response at comparable levels of performance in patients with MS, HIV, and genetic risk for AD relative to healthy controls has been observed and interpreted as compensatory overactivation 25,46,47 ; however, the opposite trend (ie, lower task-related activation at similar levels of performance) has been noted in patients at high risk for cardiovascular and cerebrovascular disease. 42,[48][49][50] On the basis these observations, it may be that early in the vascular disease process, subclinical reductions in vascular responsivity and endothelial function result in lower, yet sufficient, amounts of oxygen being delivered to activated neurons, thus producing a lower BOLD response to a cognitive challenge despite intact behavioral performance. 48,49 As vascular problems worsen, further declines in cerebrovascular reactivity and microvascular damage likely lead to vascular cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…42,[48][49][50] On the basis these observations, it may be that early in the vascular disease process, subclinical reductions in vascular responsivity and endothelial function result in lower, yet sufficient, amounts of oxygen being delivered to activated neurons, thus producing a lower BOLD response to a cognitive challenge despite intact behavioral performance. 48,49 As vascular problems worsen, further declines in cerebrovascular reactivity and microvascular damage likely lead to vascular cognitive impairment. Support is provided by a growing body of literature documenting that peripheral cardiovascular dysfunction is related to poor cerebrovascular health and diminished cognitive function in older patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The final study samples were diverse (less than 60% non-Hispanic Caucasian), well educated (average education level = 15 years), and cognitively intact (average Mini-Mental State Examination score, MMSE > 26 out of 30). We found that the intensity of working memory-related brain activation diminished with the development of metabolic and cardiovascular disorders as early as midlife, even when cognitive performance was still within normal limits [11,12,22,25,30]. These disorders included obesity, hypertension, metabolic syndrome, and frank cardiovascular diseases.…”
Section: Early Markers Of Brain Vulnerabilitymentioning
confidence: 86%
“…Lower brain activity in expected taskrelated brain regions [11,12,24,25], greater brain activity in expected task-related brain regions [15,17,19], significant recruitment of unexpected brain regions [43,44], and suspension of unrelated brain activity [22,23] have all been reported among normally performing at-risk individuals. Ubiquitous interpretations of diminished BOLD response to a cognitive challenge as both cognitive efficiency and impairment have limited our ability to extrapolate mechanisms through interpretations of isolated fMRI findings.…”
Section: Vascular and Nonvascular Mechanisms Of Cognitive Vulnerabilitymentioning
confidence: 97%
See 1 more Smart Citation